PENGEMBANGAN WISATA BAHARI PULAU GILI LABAK MELALUI DIGITAL MARKETING - Nirmalasari Idha Wijaya; Wienta Diarsvitri; Joko Subur; Herman Herman (LP2M Universitas Ibrahimy, 2023)
Gili Labak Island is located in Kombang Village, Talango District, Sumenep Madura Regency. Marine tourism in Gili Labak is in the form of beach tourism (white sand) and snorkeling tours, because Gili Labak has an unspoiled and shallow coral reef ecosystem that is easily accessible to visitors. The current problem is the socio-economic gap between the local residents of Gili Labak Island and tour agents who are people from outside the island. In addition, there is a threat of damage to the coral reef ecosystem due to the activities of tourists who do not understand the code of conduct while traveling on coral reefs. The mentoring method used in this community service is PAR (Participatory Action Research). The UHT community service team built a website with the name https://wonderfulgililabak.com/ for the promotion of Gili Labak coral reef tourism. The dissemination of tour guides on coral reefs using leaflets in the local language (Madura) was quite effective in making local people and visitors understand the importance of preserving coral reef ecosystems. The use of websites for digital marketing of marine tourism in Gili Labak is still not effective due to the limited ability of local people to manage websites.